1954
DOI: 10.1149/1.2781147
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Formation of Anodic Oxide Coatings

Abstract: The effect of variations in electrolyte and forming conditions on the formation of porous type anodic oxide coatings on aluminum are discussed, with particular reference to the manner in which these variables control oxide formation, pore development, and the thickness of the barrier layer. Formation and solution rate data are applied to show that, during the formation of a porous type coating, conditions at pore bases are vastly different from those existing in the main body of the electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 4 publications
2
29
0
Order By: Relevance
“…Also, Mason [131] and Li [132,133] found that the temperature rise at the pore bottom was higher at about 25°C, but even with this magnitude of temperature rise, the associated Joule heat would still be far insufficient to result in the observed high growth rate at the pore base. In fact Hunter and Fowle [134,135] demonstrated that the electrolyte would have to reach boiling temperature in order for such fast growth to occur. Thus, the contribution of heat assisted dissolution of oxide should only play a minor role on pore growth during anodization [130].…”
Section: Electric Field Assisted Pore Growthmentioning
confidence: 99%
“…Also, Mason [131] and Li [132,133] found that the temperature rise at the pore bottom was higher at about 25°C, but even with this magnitude of temperature rise, the associated Joule heat would still be far insufficient to result in the observed high growth rate at the pore base. In fact Hunter and Fowle [134,135] demonstrated that the electrolyte would have to reach boiling temperature in order for such fast growth to occur. Thus, the contribution of heat assisted dissolution of oxide should only play a minor role on pore growth during anodization [130].…”
Section: Electric Field Assisted Pore Growthmentioning
confidence: 99%
“…For steady-state pore growth, the velocity of the m/o-and o/e-interfaces should be balanced, keeping the barrier layer thickness (t b ) constant. This balance has long been attributed to an equilibrium between the oxide formation at the m/o-interface and the removal of oxide at the o/e-interface either by Joule's heat-induced chemical dissolution [24][25][26][27][28] or by field-assisted oxide dissolution [26,[29][30][31][32][33]. But, recent studies have indicated that the dissolution-based pore formation model is operative for the initial stage of pore formation [34][35][36], whereas it does not adequately account for the steady-state pore formation.…”
Section: Structure Of Porous Anodic Aluminum Oxide (Aao) and Its Formmentioning
confidence: 99%
“…Mason [166] and Li [162,167] found that the temperature rise at the pore bottom was higher at about 25°C, but even with this magnitude of temperature rise, the associated Joule heat would still be far insufficient to result in the observed high growth rate at the pore base. In fact Hunter and Fowlep [168,169] demonstrated that the electrolyte would have to reach boiling temperature in order for such fast growth to occur.…”
Section: Formation Mechanisms Of Anodic Porous Aluminamentioning
confidence: 99%